PROSES REDUPLIKASI PADA TEKS TERJEMAHAN AL-QUR’AN SURAH AL -WAQIAH - Andi Puspitasari; Rahmat Rahmat (Universitas Negeri Makassar)
The Process of Duplication of the Quranic Translation Text Surah Al -Waqiah. This study aims to describe the process of duplication in the translated text of the Quran Surah Al Waqiah. Qualitative type of descriptive research. The results of this study there are four types of duplication that occur, namely the repetition of all basic forms, partial repetition, repetition with affixing, and repetition of phoneme changes. Themeaning of duplication found is the meaning of 'many', the meaning of 'the deeds which are in the basic form of being done over and over again', the meaning of 'mutual', the meaning of 'level', expressing the meaning of 'very', expressing the meaning of 'resembling', and expressing the meaning of 'the highest level'. The conclusion of this study is that the discovery of the duplication process in the translation text of the Quran Surah Al Waqiah implies that the learning material for the duplication process in students and students can be taken from the translation text of theQuran.